Perspektif Peniaga Kecil Wanita Terhadap Program Mikro Kredit Al-Rahnu Maidam Di Bandaraya Kuala Terengganu - Taha Hsni, Emy Norlyana (2023)
This study indicates that the empowerment of small business women through the support of Ar-Rahnu micro credit financing is able to create a sustainable ecosystem and develop resilience of small business owners in an increasingly complex and challenging business environment. There are three (3) objectives in this study, namely to identify Ar-Rahnu's focus towards empowering women entrepreneurs, analyzing the strengths, weaknesses, opportunities and threats of Ar-Rahnu in helping small business women in Kuala Terengganu City to manage their working capital and evaluate the goals and views of these business women in Kuala Terengganu City towards the Ar-Rahnu micro loans scheme in sustaining business.